New directions in queer oral history : archives of disruption - Summerskill, Clare; Tooth Murphy, Amy, 1981-; Vickers, Emma (Abingdon, Oxon ; New York, NY : Routledge, 2022)
"This comprehensive international collection reflects on the practice, purpose and functionality of queer oral history, and in doing so, demonstrates the vibrancy and innovation of this rapidly evolving field. Drawing on the roots of oral history's original commitment to 'history from below', queer oral history has become an indispensable methodology at the heart of queer studies. Expanding and extending the existing canon, this book offers up key observations about queer oral history as a methodology, and how it might be advanced through cutting edge approaches. The collection contains a mix of contributions from established scholars, early career researchers, postgraduate students, archivists and activists, ensuring its accessibility and wide appeal. The go-to reference for queer oral history for scholars, undergraduate and postgraduate students, and community-engaged practitioners, New Directions in Queer Oral History advances rigorous methodological and theoretical debates and constitutes a significant intervention in the world of oral history"--
Keywords: Gays -- History; Sexual minorities -- History; Oral history; HISTORY / Historiography; HISTORY / Modern / 20th Century; HISTORY / Modern / 21st Century